2017
DOI: 10.1007/s10562-017-2169-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Irradiation on the Catalytic Activity of Palladium Supported Catalysts in the One-Step Isomerisation of Cinchona Alkaloids to Δ3,10-Isobases

Abstract: R=OMe: quinidine R=H: cinchonine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In recent years, the use of ionizing radiation to enhance the structure and properties of nanoscale structures has become one of the promising areas of modern materials science [1]. In addition to the large-scale application in the synthesis of nanoscale structures [2,3], the use of microwave [4], X-ray [5] and gamma radiation [6,7], as well as the processing by accelerated electron beams [8,9] and ions [10] allows directed modification of both the crystal structure and the functional properties of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of ionizing radiation to enhance the structure and properties of nanoscale structures has become one of the promising areas of modern materials science [1]. In addition to the large-scale application in the synthesis of nanoscale structures [2,3], the use of microwave [4], X-ray [5] and gamma radiation [6,7], as well as the processing by accelerated electron beams [8,9] and ions [10] allows directed modification of both the crystal structure and the functional properties of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to traditional methods such as crushing, soaking extraction and modern methods such as supercritical fluid extraction, we conclude that treatment with microwave radiation is the only way to detect the berberine, so the use of microwave extraction demonstrated superior antibacterial ability. Lipińska et al [ 107 ] found that the high energy provided by microwave radiation promoted formation of the transition state in alkaloid isomerization which in turn accelerated structural changes. Under microwave catalysis, the site of isomerization reactions is more selective, resulting in higher purity of product (Fig.…”
Section: Transformation Of Natural Productsmentioning
confidence: 99%